Comments on “Anatomically distinct fibroblast subsets determine skin autoimmune patterns” - Chen, Yudi; Chang, Jianmin (Chinese Medical Journal, 2022)
[...]this study further revealed that in the pathogenesis of vitiligo, IFNγ-responsive dermal fibroblasts are not only uniquely required but also sufficient to induce local aggregation of CD8+ T cells. [...]blocking the activation signals may be a key approach to targeting fibroblasts. [...]targeting these chemokine-chemokine receptor signaling and the downstream signaling proteins JAK1, JAK2, and STAT1 may also deserve further investigations. [...]we can perform gene ontology analysis on the transcriptome of fibroblast subtypes in mouse models and vitiligo patients to figure out the specific enrichment of IFN-γ pathway gene cell subsets. In the future, depleting vitiligo-specific pathogenic fibroblast subsets through targeting the potential distinct surface markers may serve as a possible treatment strategy.